2008
DOI: 10.1088/0963-0252/17/3/035003
|View full text |Cite
|
Sign up to set email alerts
|

Self-consistent simulation of very high frequency capacitively coupled plasmas

Abstract: A two-dimensional plasma model that includes the full set of Maxwell equations is used to understand the physics of very high frequency capacitively coupled plasmas. The effect of radio frequency (RF) source power, inter-electrode gap and gas mixture (Ar, Ar/SF 6 , Ar/CF 4 ) on the plasma characteristics is investigated. The computational results show that the plasma spatial profile is influenced by both electrostatic and electromagnetic effects. The electrostatic power deposition is stronger at the electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 14 publications
4
82
0
Order By: Relevance
“…This behavior is due to the standing electromagnetic wave effect, and it has been well characterized in previous studies. 5,7 To elucidate, we have plotted electron electrostatic power deposition ͓P e ͑ES͔͒ and electron electromagnetic power deposition at 60 MHz ͓P e ͑60͒ ͑EM͔͒ and 180 MHz ͓P e ͑180͒ ͑EM͔͒ in Fig. 1.…”
Section: Computational Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This behavior is due to the standing electromagnetic wave effect, and it has been well characterized in previous studies. 5,7 To elucidate, we have plotted electron electrostatic power deposition ͓P e ͑ES͔͒ and electron electromagnetic power deposition at 60 MHz ͓P e ͑60͒ ͑EM͔͒ and 180 MHz ͓P e ͑180͒ ͑EM͔͒ in Fig. 1.…”
Section: Computational Resultsmentioning
confidence: 99%
“…Chabert et al 6 developed a transmission line model for capacitive discharges and used it to understand the plasma behavior in the capacitive ͑E͒ and inductive ͑H͒ modes of operation. Rauf et al 7 developed a two-dimensional plasma model for VHF plasmas that includes the full set of Maxwell equations. Their studies showed that the plasma spatial profile at VHF is influenced by both electrostatic and electromagnetic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several theoretical studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and experimental research [22][23][24][25][26][27][28][29][30] have been published on the plasma characteristics in a CCP sustained by VHF sources. Lieberman et al 6 first employed a uniform slab model to investigate the standing-wave and skin effects in VHF discharges.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al 11 focused on the coupling of the electromagnetic effects with the electrostatic edge effect in a two-dimensional axisymmetric model, and they observed the so-called stop band at higher frequencies and higher pressures. Rauf et al 12,13 developed a fluid model to simulate an argon plasma, discovering that the plasma density peaked at the chamber center under the condition where the electromagnetic effects were predominant. Furthermore, they also observed that the plasma became more uniform for a small interelectrode gap at 180 MHz.…”
Section: Introductionmentioning
confidence: 99%